2015
DOI: 10.1175/jas-d-14-0202.1
|View full text |Cite
|
Sign up to set email alerts
|

Sounding-Based Thermodynamic Budgets for DYNAMO

Abstract: The Dynamics of the Madden–Julian Oscillation (DYNAMO) field campaign, conducted over the Indian Ocean from October 2011 to March 2012, was designed to study the initiation of the Madden–Julian oscillation (MJO). Two prominent MJOs occurred in the experimental domain during the special observing period in October and November. Data from a northern and a southern sounding array (NSA and SSA, respectively) have been used to investigate the apparent heat sources and sinks (Q1 and Q2) and radiative heating rates Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
116
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 118 publications
19
116
0
Order By: Relevance
“…In contrast, the MJOs simulated in the INH, SHC, and M-TDK experiments all reproduce the observed extension of diabatic heating well, especially in the INH and M-TDK. The result here suggests that the modified schemes are able to capture the development of shallow and congestus clouds before the onset of the MJO deep convection, which is consistent with the observed transition from congestus clouds to deep convections (Johnson et al 1999(Johnson et al , 2015Kikuchi and Takayabu 2004;Katsumata et al 2009;Virts and Wallace 2010). Figure 6 indicates that the enhanced lower tropospheric diabatic heating to the east of the MJO precipitation center has rectified the MJO circulation structure at the lower troposphere, such as at 850 hPa.…”
Section: Causes Of Improved Mjo Simulations With the Modified Tdk Schsupporting
confidence: 80%
See 2 more Smart Citations
“…In contrast, the MJOs simulated in the INH, SHC, and M-TDK experiments all reproduce the observed extension of diabatic heating well, especially in the INH and M-TDK. The result here suggests that the modified schemes are able to capture the development of shallow and congestus clouds before the onset of the MJO deep convection, which is consistent with the observed transition from congestus clouds to deep convections (Johnson et al 1999(Johnson et al , 2015Kikuchi and Takayabu 2004;Katsumata et al 2009;Virts and Wallace 2010). Figure 6 indicates that the enhanced lower tropospheric diabatic heating to the east of the MJO precipitation center has rectified the MJO circulation structure at the lower troposphere, such as at 850 hPa.…”
Section: Causes Of Improved Mjo Simulations With the Modified Tdk Schsupporting
confidence: 80%
“…The spatial phase relationship between the BL convergence (sea level low pressure) and major convection is supported by observations (e.g., Madden and Julian 1972;Hendon and Salby 1994;Maloney and Hartmann 1998;Hsu and Li 2012) and is consistent with the observed westward and upward tilt of anomalous precipitation heating in the lower troposphere . It is also consistent with the "stepwise" transition from shallow/congestus to deep convection (Johnson et al 1999(Johnson et al , 2015Kikuchi and Takayabu 2004;Katsumata et al 2009). Hsu and Li (2012) found that the BL convergence-induced moistening to the east of MJO convection is a primary cause for the MJO eastward propagation, while the BL convergence is related to the heating-induced free atmosphere wave dynamics.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The red boxes along the time axis represent periods of convectively active conditions. They represent dates during which the derived latent heating profile from a sounding network Johnson et al [2015] near and north of the equator between about 70°E and 80°E does not indicate suppressed conditions as shown by Ruppert and Johnson [2015]. The vertically oriented, black, dashed lines represent dates (16 October, 18 November, and 15 December) on which a mesoscale convective system was first observed by the ground-based S-PolKa precipitation detecting radar in association with three MJO events at Addu City.…”
Section: 1002/2014jd022934mentioning
confidence: 99%
“…The vertical profile of horizontal divergence calculated from a reanalysis dataset during the CINDY/DYNAMO by Zuluaga and Houze (2013) shows a composite temporal evolution closely parallel with the present result. A CINDY/DYNAMO budget analysis itself has revealed from convective heating estimates that transitions occur from shallow to deep convective and stratiform clouds (Johnson et al 2015). A theoretical framework along the same line as above has been explored over the past decade (e.g., Peters and Bretherton 2006;Khouider and Majda 2006).…”
Section: Discussionmentioning
confidence: 99%